Polymeric nanofiber coated esophageal stent for sustained delivery of an anticancer drug - Park, Chun Gwon; Kim, Myung Hun; Park, Min; Lee, Ji Eun; Lee, Seung Ho; Park, Jung-Hwan; Yoon, Kyung-Hwan; Bin Choy, Young (Macromolecular research, 2011)
In this study, we developed an esophageal stent capable of sustained delivery of an anticancer drug, fluorouracil (5-FU). The stents were coated with drug-loaded poly(lactic- co -glycolic acid) (PLGA) nanofibers (DPN) via the electrospinning method, which exhibited a sustained drug release for up to 6 days. To prolong drug release, we also added the nanofiber layers composed of PLGA alone (PN), surrounding the DPN layer, as a more resistive diffusion barrier, where a period of drug release could be extended to 21 days with the DPN layer topped with another 192 μm thick PN layer. Therefore, we envisioned longer period of drug release with the thicker PN layers, obtained simply with a longer collection time of PLGA nanofibers via electrospinning. Overall, we concluded that the drug-delivery esophageal stent prepared in this study is promising in the long-term treatment of dysphagia caused by esophageal cancer.